Track Record Model in Employee Performance Optimization Using Weight Product Method - Safrizal; Lili Tanti; Surbakti, Dio Febrian; Nurainun (Yayasan Kita Menulis, 2025)
Employee performance improvement is a crucial aspect for the growth and success of a company, especially in the agricultural sector that relies on the quality and competence of human resources. However, subjective and manual employee assessments often face challenges, such as high levels of subjectivity and the time required to complete the process. To overcome these obstacles, this study proposes the use of the Weighted Product (WP) method as an approach to building a track record model in employee performance assessment. This study involves several methodological stages, first by studying the literature related to decision support systems, WP methods, track records, and employee performance assessments. Furthermore, data collection is carried out from a dataset that includes monthly assessments of employee performance based on several criteria such as attendance, cooperation, work quantity, responsibility, and others. The next process involves modeling, where the WP model is designed to produce the maximum total value of the existing assessment criteria. Model validation is carried out through two approaches, namely the Criterion-related Validity Test and the Internal Consistency Test. The test results show that the WP model has a Criterion-related Validity of 0.9851, indicating a strong relationship between the employee scores generated and the assessments given by the supervisor. In addition, Cronbach's alpha reached a value of 1.0, indicating excellent internal reliability of the model. Thus, the use of the WP method in the employee performance tracking system can be considered effective and can improve objectivity and efficiency in employee performance assessment in the context of agricultural companies. This method not only helps in identifying high-performing employees, but also in motivating them to achieve the highest performance standards, which in turn can improve the overall operational quality and reputation of the company